Antibacterial Plasma Polymer Coatings on 3D Materials for Orthopedic Applications - Aiken Dao; Christale Gaitanos; Sumedh Kamble; Omid Sharifahmadian; Richard Tan; Steven G. Wise; Tiffany Lai Yun Cheung; Marcela M.M. Bilek; Paul B. Savage; Aaron Schindeler; Behnam Akhavan (Advanced Materials Interfaces, 2024)
Abstract Covalent biofunctionalization of implant surfaces using anti microbial agents is a promising approach to reducing bone infection and implant failure. Radical‐rich, ion‐assisted plasma polymerized (IPP) coatings enable surface covalent biofunctionalization in a simple manner; but until now, they are limited to only 2D surfaces. Here a new technology is demonstrated to create homogenous IPP coatings on 3D materials using a rotating, conductive cage that is negatively biased while immersed in RF plasma. Evidence is provided that under controlled energetic ion bombardment, this technology enables the formation of highly robust and homogenous radical‐rich coatings on 3D objects for subsequent covalent attachment of antimicrobial agents. To functionally apply this technology, the broad‐spectrum antimicrobial CSA‐90 is attached to the surfaces, where it retained potent antibacterial activity against Staphylococcus aureus. CSA‐90 covalent functionalization of stainless‐steel pins used in a murine model of orthopedic infection revealed the highly promising potential of this coating system to reduce S. aureus infection‐related bone loss. This study takes the previous research on plasma‐based covalent functionalization of 2D surfaces a step further, with important implications for ushering in a new dimension in the biofunctionalization of 3D structures for applications in bone implants and beyond.